Quantum dots, quantum dot composites and preparation methods thereof, and quantum dot products

By surface modification of quantum dots and using dithiozone salt-polythiol compounds to form an interpenetrating network structure, the problem of poor stability of quantum dot photoluminescent film is solved, and effective protection and optical performance of quantum dots are achieved Improvement.

CN115820241BActive Publication Date: 2025-02-11SUZHOU XINGSHUO NANOTECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211589352.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-12
Publication Date
2025-02-11
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

The quantum dot photoluminescent film cannot withstand high water oxygen, high temperature and high energy blue light for a long time, resulting in poor stability, which limits its industrialization and development.

Method used

By surface modification of quantum dots, dithiozone salt-polythiol compounds are used as organic ligands to form modified quantum dots, and an interpenetrating network structure is formed through the condensation reaction between these quantum dots, covering the quantums Point the body to improve its stability.

Benefits of technology

Effectively protect quantum dots from water oxygen, high temperatures, and strong blue light, significantly enhance their stability, and improve optical performance, so that the brightness and electrophotographic efficiency of quantum dot products are maintained at a high rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115820241B_ABST
    Figure CN115820241B_ABST
Patent Text Reader

Abstract

The present application provides quantum dots, quantum dot complexes, and methods for preparing the same, as well as quantum dot products. The surface-modified quantum dots of the present application include a quantum dot body and an organic ligand modified on the surface of the quantum dot body, wherein the organic ligand is derived from a zinc disulfide salt-polythiol compound, and the zinc disulfide salt-polythiol compound is obtained by reacting polythiol with a zinc disulfide salt. In the surface-modified quantum dots of the present application, the organic ligands derived from the zinc disulfide salt-polythiol compound can undergo a condensation reaction to form a quantum dot complex having an interpenetrating network structure, and the interpenetrating network structure effectively protects the quantum dots from water, oxygen, high temperature, and strong blue light. The quantum dot products prepared from the quantum dot complex have excellent optical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of display technology, and specifically relates to quantum dots, quantum dot composites and preparation methods thereof, and quantum dot products. Background Art

[0002] Quantum dots, also known as semiconductor nanocrystals, are a new type of semiconductor nanomaterial with a size of 1-10nm. Due to the quantum size effect and dielectric confinement effect, they have unique photoluminescence (PL) and electroluminescence (EL) properties. Compared with traditional organic fluorescent dyes, quantum dots have high quantum yield, high photochemical stability, not easy to photolyze, as well as wide excitation, narrow emission, high color purity, and the luminescent color can be adjusted by controlling the particle size of quantum dots. Excellent optical properties have broad application prospects in the display field. Among them, quantum dot photoluminescent film has become a research hotspot as one of the most concerned applications at present.

[0003] However, at present, quantum dots cannot withstand high water oxygen, high temperature, and high-energy blue light for a long time, resulting in poor stability of quantum dot photoluminescent films prepared from them, which is not conducive to the industrialization of quantum dot photoluminescent films and seriously restricts the development of quantum dot photoluminescent films. Summary of the invention

[0004] In response to the above technical problems, the present application provides a surface-modified quantum dot, comprising a quantum dot body and an organic ligand modified on the surface of the quantum dot body, wherein the organic ligand is derived from a disulfide zinc salt-polythiol compound, and the disulfide zinc salt-polythiol compound is obtained by the reaction of the thiol group of the polythiol with the zinc ion of the disulfide zinc salt.

[0005] Further, the dithio zinc salt includes at least one of dibenzyl dithiocarbamate zinc, dialkyl dithiophosphate zinc, dibutyl dithiocarbamate zinc, diisobutyl dithiocarbamate zinc, bis(dimethylaminothiocarbamate) zinc, di-n-butyl dithiophosphate zinc, butyl dithiophosphate zinc, dialkyl aryl amino dithiophosphate zinc, dimethyl dithiocarbamate zinc, diethyl dithiocarbamate zinc, ethylphenyl dithiocarbamate zinc, and dimethyl dithiocarbamate zinc.

[0006] Furthermore, the molar ratio of the polythiol to the dithiozinc salt is (1-4):1.

[0007] The present application also provides a quantum dot composite, comprising a quantum dot body and an interpenetrating network structure coated and connected to the quantum dot body, wherein the interpenetrating network structure is formed by the reaction between the organic ligands of a plurality of the surface-modified quantum dots as described above.

[0008] The present application also provides a method for preparing surface-modified quantum dots, comprising step S1: modifying the initial quantum dots with organic ligands to form the surface-modified quantum dots as described above.

[0009] Furthermore, the step S1 comprises:

[0010] S111, reacting the initial quantum dots with polythiol to form first quantum dots with surface modified polythiol ligands;

[0011] S112, reacting the first quantum dots with a zinc disulfide salt to form surface-modified quantum dots, wherein the surface of the surface-modified quantum dots is modified with an organic ligand, and the organic ligand is derived from a zinc disulfide salt-polythiol compound;

[0012] Preferably, the reaction temperature of step S111 is 25-100° C., and the reaction time is 6-48 h. The reaction temperature of step S112 is 45-80° C., and the reaction time is 0.5-24 h.

[0013] Furthermore, the step S1 comprises:

[0014] S121, reacting polythiol with dithiozinc salt to form dithiozinc salt-polythiol compound;

[0015] S122, reacting the initial quantum dots with a zinc disulfide salt-polythiol compound to form surface-modified quantum dots, wherein the surface of the surface-modified quantum dots is modified with an organic ligand, and the organic ligand is derived from the zinc disulfide salt-polythiol compound;

[0016] Preferably, the reaction temperature of step S121 is 60-120° C., and the reaction time is 0.5-24 h. The reaction temperature of step S122 is 25-60° C., and the reaction time is 10-48 h.

[0017] The present application provides a method for preparing a quantum dot complex, comprising step S3: causing a condensation reaction between the organic ligands in the surface-modified quantum dots to form an interpenetrating network structure, so as to obtain a quantum dot complex.

[0018] Furthermore, the reaction temperature of step S3 is 120-220° C., and the reaction time is 0.5-8 h.

[0019] The present application also provides a quantum dot product, including the quantum dot composite as described above or the quantum dot composite prepared by the method described above.

[0020] Beneficial effects: The surface-modified quantum dots of the present application include a quantum dot body and an organic ligand modified on the surface of the quantum dot body, wherein the organic ligand comes from a zinc disulfide salt-polythiol compound, and the zinc disulfide salt-polythiol compound is obtained by reacting the thiol group of the polythiol with the zinc ion of the zinc disulfide salt. The organic ligands from the zinc disulfide salt-polythiol compound in the surface-modified quantum dots can undergo a condensation reaction to form a quantum dot complex with an interpenetrating network structure. The interpenetrating network structure effectively protects the quantum dots from water oxygen, high temperature, and strong blue light. The quantum dot products prepared from the quantum dot complex have excellent optical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a reaction mechanism diagram of the quantum dot complex of Example 2 of the present application. DETAILED DESCRIPTION

[0022] The following will describe the technical solutions in the embodiments of the present application in detail in combination with the embodiments of the present application. It should be noted that the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0023] As described in the background art, the development of quantum dot photoluminescent films is severely restricted in the prior art due to the poor stability of the quantum dot photoluminescent films.

[0024] Based on this, the present application provides a surface-modified quantum dot, wherein the surface-modified quantum dot has an organic ligand modified on the surface, wherein the organic ligand is from a zinc disulfide salt-polythiol compound, wherein the zinc polythioformate-polythiol compound comprises at least two thiol end groups and a plurality of thio end groups, and wherein the zinc disulfide salt-polythiol compound is obtained by reacting the thiol of the polythiol with a zinc disulfide salt. The thiol of the polythiol reacts with zinc ions to form a zinc disulfide salt-polythiol compound, wherein the thiol on the zinc disulfide salt-polythiol compound is easily coordinated and connected with the quantum dot body, thereby obtaining a surface-modified quantum dot, wherein the zinc ions and thiol on the organic ligands between different surface-modified quantum dots undergo a polycondensation reaction with each other, thereby forming an interpenetrating network structure on the surface of the quantum dot, so as to effectively protect the quantum dot from damage by high water oxygen, excessive blue light, and high temperature.

[0025] In a specific embodiment of the present application, the polythiol includes at least one of pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol tetrakis (3-mercaptobutyrate), tris [2- (3-mercaptopropionyloxy) ethyl] isocyanurate, 1,6-hexanedithiol, 2,3-dimercapto-1-propanol, propane-1,2,3-trithiol, 2-mercaptoethyl ether, 2-mercaptoethyl sulfide, 1,8-octanedithiol, 1,8-dimercapto-3,6-dithiaoctane and trithiocyanic acid. A portion of the thiol groups in the polythiol are used for ring-opening reaction with epoxysiloxane, and another portion of the thiol groups can form a coordination connection with the surface of the quantum dots, which is beneficial for the quantum dot body to be coated by the interpenetrating network structure when preparing the quantum dot composite, thereby significantly enhancing the stability of the quantum dots.

[0026] In a specific embodiment of the present application, the zinc dithioate salt includes at least one of zinc dibenzyl dithiocarbamate, zinc dialkyl dithiophosphate, zinc dibutyl dithiocarbamate, zinc diisobutyl dithiocarbamate, zinc bis(dimethylaminothiocarbamate), zinc di-n-butyl dithiophosphate, zinc butyl dithiophosphate, dialkyl arylamino dithiophosphate, zinc dimethyl dithiocarbamate, zinc diethyl dithiocarbamate, ethylphenyl dithiocarbamate, and zinc dimethyl dithiocarbamate, so as to facilitate the effective combination reaction of the zinc dithioate salt and the polythiol.

[0027] In another specific embodiment of the present application, the molar ratio of polythiol to dithiozinc salt is (1-4):1, so that the formed surface ligand has better cross-linking degree and higher quantum efficiency in subsequent reactions.

[0028] The present application also provides a quantum dot complex, including a quantum dot body and an interpenetrating network structure coated and connected to the quantum dot body, wherein the interpenetrating network structure is formed by a condensation reaction between the organic ligands of the above-mentioned surface-modified quantum dots, and the interpenetrating network structure coats the quantum dot body, thereby providing good protection for the quantum dot body and effectively avoiding the adverse effects of high water vapor, high oxygen, high temperature, and strong blue light on the quantum dot body.

[0029] The present application also provides a method for preparing surface-modified quantum dots, including step S1: modifying the initial quantum dots with organic ligands to form the above-mentioned surface-modified quantum dots, which can further react to form quantum dot complexes to effectively avoid damage to the quantum dots by environments such as high temperature, high humidity, and strong blue light.

[0030] Further, step S1 includes:

[0031] S111, reacting the initial quantum dots with polythiol to form first quantum dots with surface modified polythiol ligands;

[0032] S112, reacting the first quantum dots with zinc disulfide salt to form surface-modified quantum dots, wherein the surface of the surface-modified quantum dots is modified with an organic ligand, and the organic ligand is derived from a zinc disulfide salt-polythiol compound.

[0033] Polythiol can be first modified onto the quantum dot body, and then zinc dithioate and polythiol are reacted, so that it is easier to obtain an organic ligand from zinc dithioate-polythiol compound that is convenient for further reaction in the subsequent step.

[0034] Preferably, the reaction temperature of step S111 is 25-100°C and the reaction time is 6-48h, and the reaction temperature of step S112 is 45-80°C and the reaction time is 0.5-24h. The reaction is carried out at a lower temperature to avoid the use of high-temperature equipment, effectively simplifying the preparation process, and obtaining an organic ligand with excellent binding properties on the quantum dot body.

[0035] Alternatively, step S1 of the present application includes:

[0036] S121, reacting polythiol with dithiozinc salt to form dithiozinc salt-polythiol compound;

[0037] S122, reacting the initial quantum dots with a zinc disulfide salt-polythiol compound to form surface-modified quantum dots, wherein the surface of the surface-modified quantum dots is modified with an organic ligand, and the organic ligand is derived from the zinc disulfide salt-polythiol compound.

[0038] That is, the zinc disulfide salt can be first reacted with polythiol to form a zinc disulfide salt-polythiol compound, and then the zinc disulfide salt-polythiol compound can be modified onto the quantum dot body to form surface-modified quantum dots. This method can effectively control the organic ligand structure formed on the quantum dot body.

[0039] Preferably, the reaction temperature of step S121 is 60-120° C. and the reaction time is 0.5-24 h, and the reaction temperature of step S122 is 25-60° C. and the reaction time is 10-48 h, and the structure of the obtained organic ligand is more controllable.

[0040] The present application also provides a method for preparing a quantum dot complex, including step S3: causing a condensation reaction between the organic ligands in the above-mentioned surface-modified quantum dots to form an interpenetrating network structure to obtain a quantum dot complex, in which the quantum dot body can be firmly protected and the influence of high water and oxygen content, high temperature, and strong blue light on the quantum dot body can be effectively avoided.

[0041] Furthermore, the reaction temperature of step S3 is 120-220° C. and the reaction time is 0.5-8 h, so that the reaction of forming the interpenetrating network structure is more complete, and the quantum dot body is better protected.

[0042] In another specific embodiment of the present application, each reaction step of the present application may include a solvent, and the solvent is selected from but not limited to at least one of n-heptane, cyclohexane, n-hexane, xylene, and chloroform. Such solvents can better dissolve polythiol, disulfide zinc salt, initial quantum dots, and surface-modified quantum dots, and form a more uniform and dense interpenetrating network structure on the surface of the quantum dot body.

[0043] The present application also provides an application of the above-mentioned quantum dot complex in the preparation of quantum dot products, wherein the quantum dot complex is added to plastic particles, curing glue or printing ink to make quantum dot products. For example, the quantum dot complex can be prepared into quantum dot glue liquid, quantum dot photoresist or quantum dot ink, and then prepared to form a quantum dot film, a quantum dot diffusion plate, a quantum dot color film, and then prepared to form a display device. When the co-extrusion technology is used to prepare the quantum dot product, the quantum dot complex needs to be ground into microspheres and then co-mixed and extruded with a polymer material to prepare a quantum dot film or a quantum dot diffusion plate.

[0044] In the present application, the initial quantum dots include at least one of a II-VI group compound, a III-V group compound, and a perovskite quantum dot. For example, the II-VI group compound may include: CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, MgSe, MgS, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgS Te, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, MgZnSe, MgZnS, HgZnT eS, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe or combinations thereof. The III-V compounds may include GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, InZnP, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb or a combination thereof. The perovskite quantum dots include organic perovskite quantum dots and / or inorganic perovskite quantum dots, and the perovskite quantum dots may be related products purchased on the market.

[0045] It can be understood that the structure of the quantum dot body of the present application comes from the initial quantum dot, for example, the structure of the quantum dot body of the present application is the core structure or core-shell structure of the initial quantum dot.

[0046] Some exemplary embodiments according to the present application are described in more detail below; however, the exemplary embodiments of the present application are not limited thereto.

[0047] Example 1

[0048] S111, preparing the first quantum dot with surface modified polythiol ligand:

[0049] 1 g of pentaerythritol tetrakis(3-mercaptopropionate) and 0.5 g of initial quantum dots (green light quantum dots: CdSe / CdSeS / ZnS) were dissolved in 20 g of xylene, and reacted at 80° C. in a nitrogen atmosphere for 12 h to form a first quantum dot solution;

[0050] S112. Preparation of surface modified quantum dots:

[0051] 2 g of zinc dibutyl dithiocarbamate was added to the first quantum dot solution obtained above, and the reaction was carried out at 35° C. in a nitrogen atmosphere for 24 h. When 10 mg of the sample could be dissolved in 3 ml of PGMEA, surface-modified quantum dots were obtained.

[0052] S3. Preparation of quantum dot complexes:

[0053] The surface modified quantum dots are heated to 120° C. and subjected to condensation reaction for 2 hours, so that the organic ligands in the surface modified quantum dots react with each other to form an interpenetrating network structure, thereby obtaining a quantum dot complex.

[0054] Example 2

[0055] S121, preparing zinc dithioate-polythiol compound:

[0056] 1 g of pentaerythritol tetrakis (3-mercaptopropionate) and 2 g of dibutyl zinc dithiocarbamate were dissolved in 20 g of xylene. The system viscosity was 94 cp. The mixture was reacted at 60 ° C in air atmosphere for 12 h to form a zinc dithioate-polythiol compound. The system viscosity was 587 cp.

[0057] S122. Preparation of surface modified quantum dots:

[0058] 1 g of a xylene solution of a zinc disulfide salt-polythiol compound was reacted with 0.5 g of initial quantum dots (green light quantum dots: CdSe / CdSeS / ZnS) at 35° C. and in a nitrogen atmosphere for 24 h to form surface-modified quantum dots, wherein the organic ligands of the surface-modified quantum dots were derived from the zinc disulfide salt-polythiol compound;

[0059] S3. Preparation of quantum dot complexes:

[0060] The surface modified quantum dots are heated to 160° C. and subjected to condensation reaction for 2 h in a nitrogen atmosphere, so that the organic ligands in the surface modified quantum dots react with each other to form an interpenetrating network structure to obtain a quantum dot complex. The reaction process is as follows: Figure 1 shown.

[0061] Example 3

[0062] This embodiment is substantially the same as Embodiment 1, except that: 2 g of zinc dibutyl dithiocarbamate in step S112 is adjusted to 1 g of zinc dialkyl dithiophosphate, and the reaction temperature in step S112 is 45° C. and the reaction time is 15 h.

[0063] Example 4

[0064] This embodiment is substantially the same as Embodiment 1, except that 1 g of pentaerythritol tetrakis(3-mercaptopropionate) in step S111 is adjusted to 1 g of tris[2-(3-mercaptopropionyloxy)ethyl]isocyanurate, the reaction temperature in step S111 is 100° C. and the reaction time is 24 h, and the reaction temperature in step S112 is 60° C. and the reaction time is 20 h.

[0065] Example 5

[0066] This embodiment is substantially the same as Embodiment 1, except that: 1 g of pentaerythritol tetrakis(3-mercaptopropionate) in step S111 is adjusted to 1 g of 1,6-hexanedithiol, the mass of zinc dibutyldithiocarbamate in step S112 is adjusted to 1 g, the reaction temperature in step S111 is 60° C. and the reaction time is 30 h, and the reaction temperature in step S112 is 80° C. and the reaction time is 24 h.

[0067] Example 6

[0068] This embodiment is substantially the same as embodiment 1, except that: the mass of pentaerythritol tetrakis(3-mercaptopropionate in step S111 is adjusted to 1.5 g, the initial quantum dots are replaced with red light quantum dots: InP / ZnS, the reaction temperature is adjusted to 25° C., and the reaction time is adjusted to 48 h; the mass of zinc dibutyl dithiocarbamate in step S112 is adjusted to 1 g, the reaction temperature is adjusted to 30° C., and the reaction time is adjusted to 10 h.

[0069] Example 7

[0070] This embodiment is substantially the same as Embodiment 2, except that: 2 g of zinc dibutyl dithiocarbamate in step S121 is adjusted to 1 g of zinc dialkyl dithiophosphate, the reaction temperature is adjusted to 85° C., and the reaction time is adjusted to 18 h; the reaction temperature in step S122 is adjusted to 50° C., and the reaction time is adjusted to 30 h. The viscosities of the system in step S121 before and after the reaction are 73 cp and 394 cp, respectively.

[0071] Example 8

[0072] This embodiment is substantially the same as Embodiment 2, except that: 1 g of pentaerythritol tetrakis (3-mercaptopropionate) in step S121 is adjusted to 1 g of tris [2- (3-mercaptopropionyloxy) ethyl] isocyanurate, the reaction temperature is adjusted to 80°C, the reaction time is adjusted to 24 h, the reaction temperature in step S122 is adjusted to 60°C, the reaction time is adjusted to 48 h, and the viscosities of the system in step S121 before and after the reaction are 173 cp and 869 cp, respectively.

[0073] Example 9

[0074] This embodiment is substantially the same as Embodiment 2, except that: 1 g of pentaerythritol tetrakis (3-mercaptopropionate) in step S121 is adjusted to 1 g of 1,6-hexanedithiol, the reaction temperature is adjusted to 120° C., the reaction time is adjusted to 20 h, the viscosities of the system before and after the reaction are 62 cp and 306 cp, respectively, the reaction temperature in step S122 is adjusted to 45° C., and the reaction time is adjusted to 40 h.

[0075] Example 10

[0076] This embodiment is substantially the same as Embodiment 2, except that: 2 g of dibutyl zinc dithiocarbamate in step S121 is adjusted to 1 g of ethylphenyl zinc dithiocarbamate, the reaction temperature is adjusted to 85° C., the reaction time is adjusted to 15 h, and the viscosities of the system before and after the reaction are 87 cp and 475 cp, respectively; the reaction temperature in step S122 is adjusted to 50° C., and the reaction time is adjusted to 36 h.

[0077] Comparative Example 1

[0078] This embodiment is substantially the same as Embodiment 1, except that the zinc dibutyl dithiocarbamate in step S112 is removed.

[0079] Comparative Example 2

[0080] This comparative example is substantially the same as Example 1, except that 1 g of pentaerythritol tetrakis(3-mercaptopropionate) in step S111 is adjusted to dodecanethiol, and zinc dibutyldithiocarbamate in step S112 is removed.

[0081] Comparative Example 3

[0082] This comparative example is substantially the same as Example 6, except that pentaerythritol tetrakis(3-mercaptopropionate) in step S111 is removed, the reaction temperature in step S112 is adjusted to 25° C., and the reaction time is adjusted to 6 h.

[0083] Comparative Example 4

[0084] This comparative example is substantially the same as Example 2, except that 1 g of pentaerythritol tetrakis(3-mercaptopropionate) in step S121 is adjusted to 3 g of dodecanethiol, and 2 g of zinc dibutyldithiocarbamate is adjusted to 1 g of zinc dibutyldithiocarbamate. The viscosities of the system before and after the reaction are 51 cp and 198 cp, respectively.

[0085] The original QD (green light quantum dot) and 200 mg of quantum dot powder in Examples 1 to 10 and Comparative Examples 1 to 4 were respectively mixed with 20 g of polystyrene, and a quantum dot film was prepared by co-extrusion in an extruder using a step-by-step heating method from 185°C to 220°C. The aging data of the quantum dot film was tested under two aging conditions. The aging conditions were: a temperature of 60°C and a humidity of 90%, and irradiation with blue light with a brightness of 1000 nits and an emission wavelength of 447 nm. The test results are shown in Table 1.

[0086] Table 1 Quantum dot film aging data

[0087]

[0088]

[0089] It can be seen from Table 1 that compared with the initial quantum dots and the quantum dot films prepared by the quantum dots of Comparative Examples 1 to 4, the quantum dot films prepared by the quantum dot composites of Examples 1 to 10 of the present application have strong anti-aging ability, high brightness and EQE maintenance rate, indicating that the quantum dot composites prepared by the technical scheme of the present application have good stability, and the quantum dot films prepared therefrom have high stability, which is conducive to promoting the commercial application of optical components containing quantum dots.

[0090] Although the inventors have elaborated and enumerated the technical solutions of the present application in detail, it should be understood that it is obvious for those skilled in the art to modify and / or adapt the above embodiments or adopt equivalent alternative solutions, which cannot deviate from the essence of the spirit of the present application. The terms appearing in the present application are used to explain and understand the technical solutions of the present application and cannot constitute limitations on the present application.

Claims

1. A method for preparing a quantum dot complex, characterized in that: The method comprises step S1: modifying the initial quantum dots with organic ligands to form surface-modified quantum dots; the surface-modified quantum dots comprise a quantum dot body and an organic ligand modified on the surface of the quantum dot body, the organic ligand is from a zinc disulfide salt-polythiol compound, and the zinc disulfide salt-polythiol compound is obtained by reacting polythiol with zinc disulfide salt; the molar ratio of the polythiol to the zinc disulfide salt is (1-4):1; The method comprises step S3: causing a condensation reaction between the organic ligands in the surface-modified quantum dots to form an interpenetrating network structure, so as to obtain a quantum dot complex.

2. The method for preparing the quantum dot composite according to claim 1, characterized in that: The step S1 comprises: S111, reacting the initial quantum dots with polythiol to form first quantum dots with surface modified polythiol ligands; S112, reacting the first quantum dots with zinc disulfide salt to form surface-modified quantum dots, wherein the surface of the surface-modified quantum dots is modified with an organic ligand, and the organic ligand is derived from a zinc disulfide salt-polythiol compound.

3. The method for preparing the quantum dot composite according to claim 1, characterized in that: The step S1 comprises: S121, reacting polythiol with dithiozinc salt to form dithiozinc salt-polythiol compound; S122, reacting the initial quantum dots with a zinc disulfide salt-polythiol compound to form surface-modified quantum dots, wherein the surface of the surface-modified quantum dots is modified with an organic ligand.

4. The method for preparing the quantum dot composite according to claim 1, characterized in that: The reaction temperature of step S3 is 120-220° C., and the reaction time is 0.5-8 h.

5. The method for preparing the quantum dot composite according to claim 1, characterized in that: The zinc dithioate salt includes at least one of zinc dibenzyl dithiocarbamate, zinc dialkyl dithiophosphate, zinc dibutyl dithiocarbamate, zinc diisobutyl dithiocarbamate, zinc bis(dimethylaminothiocarbamate), zinc di-n-butyl dithiophosphate, zinc butyl dithiophosphate, zinc dialkyl arylamino dithiophosphate, zinc dimethyl dithiocarbamate, zinc diethyl dithiocarbamate, zinc ethylphenyl dithiocarbamate, and zinc dimethyl dithiocarbamate.

6. A quantum dot product, characterized in that: The invention comprises a quantum dot composite prepared by the method described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Quantum dot aggregate particles, production methods thereof, and compositions, compounds and electronic devices including the same

    CN107722184A